Workers, worshippers, and the servant of the temple: Up-country Tamil religiosity at Sri Pāda/ Shivanoli Pādam - de Silva, P. (University of Colombo, 2017)
The presence of Up-country Tamil Hindu persons as worshippers at the sacred footprint (Sri Pāda) is quite recent when compared to other ethno-religious groups in the country. The majority of pilgrims going toSri Pāda are Sinhala Buddhists, and the second largest group are Hindu Tamils from the tea estates in the area around the temple. But unlike in the past, Hindu, Muslim, and Catholic groups do not play any significant ritual role at the temple. As far as Up-country Tamils’ religiosity is concerned, the central religious festival that they perform annually is centered on the female goddess Mariyamman. By celebrating Mariyamman, Up-country Tamils highlight their distinct identification with the island and their cultural differences from not only other ethnic groups in Sri Lanka but also diasporic Tamil Hindu communities. This is because the cult of Mariyamman is quite a unique feature of Upcountry Tamil religiosity when compared to other Hindu practices in the country. However, Up-country Tamils are not confined to their own religious world, and the performance of their rituals can be extended to major multi-religious sacred sites like Kataragama, Munneswaram, and Sri Pāda. This paper elaborates how they have connected with the Buddhist-dominated Sri Pāda as worshippers and become the servants of the Sri Pāda temple while being estates workers. This paper will also explain the politics of carving out a ritual space by performing a special ritual at the Sri Pada temple and how such a ritual of Up-country Tamils highlights their cultural differences from numerous others, including Sinhalas and other Tamil Hindu communities.
Keywords: Up-country Tamils, religiosity, ethnicity